Observation of Clouds Using the CSIR Transportable LIDAR: A Case Study over Durban, South Africa - Lerato Shikwambana; Venkataraman Sivakumar (Advances in Meteorology)
The Council for Scientific and Industrial Research (CSIR) transportable Light Detection And Ranging (LIDAR) was used to collect data over Durban (29.9°S, 30.9°E) during 20–23 November 2012. Aerosol measurements have been carried out in the past over Durban; however, no cloud measurements using LIDAR have ever been performed. Therefore, this study further motivates the continuation of LIDAR for atmospheric research over Durban. Low level clouds were observed on 20–22 November 2012 and high level clouds were observed on 23 November 2012. The low level cloud could be classified as stratocumulus clouds, whereas the high level clouds could be classified as cirrus clouds. Low level cloud layers showed high extinction coefficients values ranging between 0.0009 and 0.0044 m−1, whereas low extinction coefficients for high level clouds were observed at values ranging between 0.000001 and 0.000002 m−1. Optical depth showed a high variability for 20 and 21 November 2012. This indicates a change in the composition and/or thickness of the cloud. For 22 and 23 November 2012, almost similar values of optical depth were observed. Cloud-Aerosol LIDAR and Infrared Pathfinder Satellite Observations (CALIPSO) revealed high level clouds while the CSIR LIDAR could not. However, the two instruments complement each other well to describe the cloudy condition.